Urgency in Conservation of the Brazilian Pampa Biome: Endangered Species and Environmental Legislation - Almeida, Giovani Spinelli de; Silva, Anderson Moraes da (Technical and Scientific Journal Green Cities, 2025)
Objective – This study aims to identify endangered species in the Pampa biome, assess their conservation status, and verify the existence of a specific legal framework for its protection. Methodology – The research was conducted through data analysis from official databases of the Ministry of the Environment and Climate Change on endangered species (2020 list), along with legislative reviews from the Planalto website and the Legislative Assembly of the State of Rio Grande do Sul. Originality/relevance – The study highlights the lack of a specific legal framework for the protection of the Pampa biome, emphasizing the urgent need for public policies to support its conservation. The research contributes to discussions on biodiversity and biome preservation in Brazil, focusing on the Pampa, which still lacks effective protection measures. Results – The findings indicate that the Pampa biome hosts 12,503 known species, of which 92 are classified as endangered under categories such as Critically Endangered, Endangered, and Vulnerable. Furthermore, the study reveals the absence of a specific legal framework for its protection, reinforcing the necessity for public policies and expansion of conservation units in the region. Theoretical/methodological contributions – The research presents an integrated analysis of biodiversity and environmental legislation, identifying legal gaps that hinder the conservation of the Pampa biome. Additionally, it suggests guidelines for the establishment of a legal framework tailored to the biome’s specific needs. Social and environmental contributions – The study underscores the urgency of implementing public policies and environmental education initiatives aimed at conserving the Pampa biome. It highlights the importance of community participation and the creation of new conservation areas to safeguard biodiversity and promote ecological sustainability.